Recurrent miscarriage in North Indian population: a study of association of polymorphisms in genes coding for the natural killer: cell receptor natural killer group 2, member D and its ligand MHC class I chain-related protein A - Rawool, Anup; Gupta, Satyaprakash; Singh, Bharti; Phadke, Shubha R; Saxena, Deepti; Mandal, Kausik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this present study was to investigate the possible association of natural killer group (NKG) receptors gene polymorphisms and MHC class I chain-related protein A (MICA) gene polymorphism with recurrent spontaneous abortion (RSA). Methods: Three single-nucleotide polymorphism (SNPs) in NKG2D gene (rs2255336, rs2617160 and rs2617170) and one SNP in MICA gene (MICA129) rs1051792 were assessed in 100 controls and 100 patients employing polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and agarose gel electrophoresis. Results: NKG2D (rs2617160) and MICA 129 (rs1051792) variants are associated with RSA risk in North Indian women. Conclusions: The NKG2D and MICA129 gene polymorphisms may influence the success of pregnancy in North Indian women population.